(untitled) (Ameghiniana, 2013)
The first calcareous microfossils (ostracods, charophytes and foraminifers) found in Ranquiles Formation suggest Lower Cretaceous age for it; and, for some levels, brackish-continental environment. Four new species of ostracods are described.